Pembagian Peran Suami Istri di Desa Sidodadi Bangilan Kabupaten Tuban Perspektif Gender dan Hukum Islam - Arina Fiddaroini .; Fathonah K. Daud; Fira Mubayyinah (Universitas Islam Lamongan, 2022)
This study discusses the division of husband and wife roles in the family in Sidodadi Village, Bangilan District, Tuban Regency. This study aims to understand the division of husband and wife roles in the family in Sidodadi Village, Bangilan District, Tuban Regency and to understaand the overview of gender equality and Islamic law on the division of husband and wife roles in the family in Sidodadi Village, Bangilan District, Tuban Regency. This study uses a qualitative method, namely the author collects data from the informants and then compares the sources with each other. The results of this study indicate that the lfe of Sidodadi Bangilan Tuban village community is a traditional society. The division of roles that occurs in the family in that village is divided into two groups with different role distribution patterns where first, husband and wife take roles in the public and domestic sectors; second, husbands take on public roles and wives take on public and domestic roles. The division of husband and wife roles that occurred in Sidodadi village, Bangilan district, Tuban district partly still has gender inquality. Meanwhile, according to the point of wiew of Islamic law that there is no prohibition for the wife to work, as long as both the wife and husband fulfill their rights and obligations, Islam views it as a good thing and no one is harmed.